Lenormandins A—G, new azaphilones from Hypoxylon lenormandii and Hypoxylon jaklitschii sp. nov., recognised by chemotaxonomic data - Kuhnert, Eric (2015)
Seven new azaphilone pigments named lenormandins A-G were isolated from stromata (fruiting bodies) of the xylariaceous fungus, Hypoxylon lenormandii. using preparative High Performance Liquid Chromatography (HPLC) and their structures were elucidated by NMR spectroscopy, high resolution mass spectrometry and other spectral methods. Their occurrence in herbarium specimens (including various type materials collected in the 19th and early 20th century) and several fresh collections was studied by analytical HPLC with diode array and mass spectrometric detection (HPLC-DAD/MS), revealing that this group of pigments is specific for Hypoxylon lenormandii from various geographic regions and otherwise only occurs in closely related taxa, i.e. H. sublenormandii and an undescribed fungus from Sri Lanka, for which we propose the name H. jaklitschii. The status of the new species was established by using molecular phylogenetic data based on ITS and partial beta-tubulin sequences, and by detailed morphological studies.